Experimental thermal performance evaluation of different configurations of Copenhagen solar cooker - Apaolaza-Pagoaga, Xabier; Carrillo-Andrés, Antonio; Rodrigues-Ruivo, Celestino (Elsevier, 2021)
In this work, four different configurations of Copenhagen solar cookers were tested experimentally at the same time under the same weather conditions. First tests were carried out using pots without water load. Secondly, tests were performed with the equal amount of water in each pot. Thirdly, tests were carried out with different amounts of water for one of the configurations. From the results of the first set of tests, it was found that the performance of one of the configurations depends more significantly on the solar altitude angle than the others. A large number of experiments for each set of tests were conducted covering a wide range of solar altitude angles. A thermal performance analysis based on the ASAE S580.1 standard was performed with the measured data of the second and third sets of tests. The obtained plots with the observation points of each configuration evidence that the linear trend of the standardised power is not universal. The observed trends are very dependent on the solar altitude angle. Thus, the procedure for evaluating standardised power recommended by the standard for cooker performance comparison should be improved.
Keywords: Energía solar - Aplicaciones; Solar cooking; Copenhagen cooker; Experimental test; Solar energy